Great Indian speeches for children - Introduction by O'brien, Derek (New Delhi Talking Cub, 2018)
A fantastic collection of some of the most inspiring speeches from India, spanning over a century. In this book, brilliantly introduced by Derek O$1 (BBrien, legendary Indians speak on diverse topics that will motivate young readers: freedom and equal rights, science and sports, friendship and education, the environment and social responsibility, ambition and courage, the love of books and the burden of schoolbags. Even in this age of speed and bite-sized attention spans, these timeless words reach out across years and touch us, provoke us, make us think, and become a call to action.s
Keywords: Children Book; Great Indian Speeches